One‐Pot Sequence‐Controlled Synthesis of Oligosiloxanes. Issue 17 (15th March 2018) - Matsumoto, Kazuhiro; Oba, Yuki; Nakajima, Yumiko; Shimada, Shigeru; Sato, Kazuhiko
Abstract: Silicones (organopolysiloxanes) have found applications in a wide range of research areas, and their unique and valuable properties have rendered these materials virtually irreplaceable. Despite the fact that silicones have been employed industrially for more than 70 years, synthetic routes to generate silicones remain limited, and the sequence‐controlled synthesis of oligo‐ and polysiloxanes still represents a major challenge in silicone chemistry. Described here is a highly selective sequence‐controlled synthesis of linear, branched, and cyclic oligosiloxanes by simple iteration of two reactions, specifically, a B(C6 F5 )3 ‐catalyzed dehydrocarbonative cross‐coupling of alkoxysilanes with hydrosilanes and a B(C6 F5 )3 ‐catalyzed hydrosilylation of carbonyl compounds, in a single flask. The sequence of the resulting oligosiloxanes can be controlled precisely by the order of addition of the hydrosilane monomers. Abstract : An orderly approach : A one‐pot iteration of B(C6 F5 )3 ‐catalyzed dehydrocarbonative cross‐coupling of alkoxysilanes with hydrosilanes and B(C6 F5 )3 ‐catalyzed hydrosilylation of carbonyl compounds enables a highly selective sequence‐controlled synthesis of linear, branched, and cyclic oligosiloxanes. The sequence of the resulting oligosiloxanes can be controlled precisely by the order of addition of the hydrosilane monomers.